Agronomic Traits and Genetic Fidelity of Four Cocoa Clones Derived from Somatic Embryogenesis Culture - Entuni, Gibson; Nori, Hollena; Edward, Rebicca; Jaafar, Ahmad Kamil bin Mohammad (Trends in Sciences, 2022)
Morphological and genetic characterization of MCBC1, PBC230, KKM22 and KKM4 cocoa clones derived from staminode and immature zygotic embryo culture were compared with those conventionally grafted. Somatic embryogenesis culture successfully produced true-to-type progenies of elite cocoa clones of MCBC1, PBC230, KKM22 and KKM4 (from staminode culture). Phenotype variations (p < 0.05) were observed only in KKM4 clone from immature zygotic embryo culture which exhibited lower quantities in the fresh pod weight, number of flat beans per pod, seed length, seed width and individual seed weight. The genetic stability of the cultured clones was tested using fragment analysis with 12 SSR primers to validate these results. Eleven of these SSR primers detected mutations only in the allelic profiles of KKM4 clone from immature zygotic embryo. These results validated those variations in KKM4 clones of immature zygotic embryo culture were due to interactions between genotypic and explant types. Unfortunately, these variations were negative attributes to cocoa productivity. Thus, it is suggested that successful production of true-to-type KKM4 cocoa clone should consider other means of propagation including modification of the culture conditions. HIGHLIGHTS It is crucial to evaluate and confirm the quality of the immature zygotic and staminode regenerated cocoa plant before using the culture technique for commercial production The quality can be detected in both phenotype and genotype by comparing the regenerated cocoa plant with those regenerated from the conventional asexual propagation method of grafting Phenotype and genotype differences were only observed in KKM4 clone regenerated from immature zygotic embryo culture and thus validated that this clone exhibited variation KKM4 clone from immature zygotic embryo culture which has lower quantities in the fresh pod weight, number of flat beans per pod, seed length, seed width and individual seed weight confirmed the negative effect of using immature zygotic embryo explant for KKM4 clone propagation. It is suggested to modify the culture technique GRAPHICAL ABSTRACT